Diversifikasi Produk Sebagai Strategi Bertahan dan Berkembang di Masa Pandemi Desa Prima Kenanga - Sugiharti Mulya Handayani; Endang Siti Rahayu; Heru Irianto; Setyowati Setyowati; Mei Tri Sundari; Fanny Widadie (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Desa Prima is one of the policies of the Ministry of Women’s Empowerment to break the poverty chain and women empowerment through productive economic development. “Kenanga” group is one of the Desa Prima with 21 active members engaged in culinary (81%), handicraft (9.5%), and services (9.5%). During the pandemic, sales are decreasing drastically. Therefore, it is necessary to develop an alternative business to survive and develop. By using FGD (Focus Group Discussion) and the PRA (Participatory Rural Appraisal) method, these service activities aim to provide alternative product diversification. This service provided training in making “pisang sanggan” and “Jadah Wajik” as delivery in “seserahan” ceremony. This training was chosen because it is still relevant to the business field of the participants and can increase selling. The results show that the training increases participants’ understanding, skills, and creativity in making “Pisang sanggan” and “Jadah Wajik” and selling the product 100%.